2008
DOI: 10.3155/1047-3289.58.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Resuspension Rate and Residence Time of Indoor Particles

Abstract: Resuspension experiments were performed in a single-family residence. Resuspension by human activity was found to elevate the mass concentration of indoor particulate matter with an aerodynamic diameter less than 10 microm (PM10) an average of 2.5 times as high as the background level. As summarized from 14 experiments, the average estimated PM10 resuspension rate by a person walking on a carpeted floor was (1.4 +/- 0.6) x 10(-4) hr(-1). The estimated residence time for PM in the indoor air following resuspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 3 publications
5
94
1
Order By: Relevance
“…Long et al (2000) reported mean peak concentrations for PM 2.5 during dusting and vigorous walking to be 23 ± 23 µg m −3 and 12 ± 9.1 µg m −3 above background, respectively. Although not directly comparable, Qian et al (2008) estimated the mean peak concentration of PM 10 to be 37 ± 24 µg m −3 above background for one person walking in a residence. The difference might be due to the difference in particle composition and size distribution between the ATD and the residential dust, the activity resuspending the particles, and/or the mixing volume and air change rate.…”
Section: Assessment Of Well-mixed Volumementioning
confidence: 92%
See 1 more Smart Citation
“…Long et al (2000) reported mean peak concentrations for PM 2.5 during dusting and vigorous walking to be 23 ± 23 µg m −3 and 12 ± 9.1 µg m −3 above background, respectively. Although not directly comparable, Qian et al (2008) estimated the mean peak concentration of PM 10 to be 37 ± 24 µg m −3 above background for one person walking in a residence. The difference might be due to the difference in particle composition and size distribution between the ATD and the residential dust, the activity resuspending the particles, and/or the mixing volume and air change rate.…”
Section: Assessment Of Well-mixed Volumementioning
confidence: 92%
“…Thatcher and Layton (1995) estimated resuspension rates on the order of 10 −5 -10 −4 hr −1 for supermicron particles and 10 −7 hr −1 for 0.4-1 µm particles for four people performing normal activities in a residence. Qian et al (2008) found the average resuspension rates for PM 10 to be (1.4 ± 0.6) × 10 −4 hr −1 from 14 experiments for a person walking on a carpeted floor in a residence. Karlsson et al (1999) introduced the dimensionless resuspension fraction r ja that was defined as the fraction of particles emitted from the contact area (e.g., area of sole and heel of one shoe) during one cycle of activity (e.g., one foot step).…”
Section: Introductionmentioning
confidence: 98%
“…The removal forces, required to dislodge the particle from a surface, can be mechanical, vibrational, or hydrodynamic. Since major mechanisms of indoor particle resuspension, i.e., human activity and HVAC systems, are largely due to fluid motion [6,9,10], we will only consider hydrodynamic removal forces and disregard the others.…”
Section: Physical Mechanisms Responsible For Resuspensionmentioning
confidence: 99%
“…However, vacuuming is also reported to be an effective tool to decrease the floor loading, and to shorten the overall indoor air residence time of a particulate pollutant (Qian et al, 2008). In this study three vacuuming schedules were examined: a week before the prayer day, a day before the prayer day, and in the morning of the prayer day.…”
Section: Particle Number Concentrationsmentioning
confidence: 99%
“…Human activities, especially vacuuming have been reported to increase the concentrations 1.2 times to 29.5 times depending on the particle size (Thatcher and Layton, 1995;Corsi et al, 2008;Qian et al, 2008). Overall 46e93% (25 and 75 percentile values, respectively) of the PM 2.5 was found to originate from the outdoors with a median value of 56% (Meng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%